Aesthetic surprises and considerations when researching marine science education with art - Hannigan, Shelley M.; Freitas, Cátia; Francis, Prue (Frontiers in Education, 2023)
My abstract has been accepted to this special issue on Disciplinary Aesthetics. This paper shares the mixed methodology used by focusing on the qualitative methods used, that arose out of a need to understand the role of aesthetics in this research project. This paper documents the analysis of data that included children's drawings and dialogue between researchers and children from interviews. We discuss insights into the role of aesthetics that were revealed in the visual and narrative data from perspectives of children's learning and how the researchers were able to understand this. These findings are discussed considering the teaching intentions and procedures used, the importance of this multimodal approach to research that revealed aesthetics of science, visual art and language in education.